KORELASI ANTARA SIKAP TOLERANSI DENGAN INTERAKSI SOSIAL DI KELAS SISWA KELAS IV SD GUGUS VII KUTA SELATAN TAHUN PELAJARAN 2017/2018 - Ni Kadek Manika Sari Manika Sari (Universitas Pendidikan Ganesha, 2018)
The purpose of this research was to find out the correlation between tolerance attitudes with social interaction in Elementary School Gugus VII Kuta Selatan Grade 4. The type of this research was ex post facto. Research populationswere all students Grade 4 in Elementary School Gugus VII Kuta Selatan academic period 2017/2018 which has population over 123 students. Sample was determined by proportional technique random sampling with the level of error 5% and the number of sample gained from the populations were 89 students. The data from tolerance attitudes and social interactions were obtained through questionnaire which was answered by the respondents. The prerequisite test was data distribution normality test. After all the prerequisite test fulfilled, statistics analysis that was used in this research is hypothesis test using correlation analysis product moment. Based on the analysis result we found that rcount = 1,205. At a level of signification 5% with n= 89, obtained rtable= 0,213. Because rcount= 1,205 >rtable= 0,213 it means that H0 that said there is no significant correlation between tolerance attitudes with social interactions in Elementary School Gugus VII Kuta Selatan Grade 4 academic period 2017/2018 was rejected and Ha was accepted . The conclusion was there is correlation between tolerance attitudes with social interactions in in Elementary School Gugus VII Kuta Selatan Grade 4, with positive correlation line, which means the higher tolerance attitudes will increase the social interactions in the class.Keywords: tolerance attitude, social interactions in the class